Microtubule organization during rabbit fertilization by intracytoplasmic sperm injection with and without sperm centrosome - MORITA, JUNKO (Reprod Med Biol, 2005)
Aim: In most mammalian fertilization, the sperm introduces the centrosome, which acts as a microtubule organizing center (MTOC) and is essential for pronuclear movement. In rabbit fertilization, biparental centrosomal contribution in microtubule organization has been suggested. Methods: To reveal the function and inheritance of the centrosome during rabbit fertilization, we compared microtubule organization and early embryonal development following intracytoplasmic sperm injection (ICSI) with and without sperm centrosome. Sperm centrosome was removed by sonication, and the isolated sperm head was injected by a Piezo‐driven micromanipulator. Samples were studied by light microscope after immunocytological stain. Results: The sperm aster formation was observed 2–3 h after ICSI with intact sperm. In contrast, microtubules were organized between the male and female pronucleus without a nucleation site in the eggs after ICSI with an isolated sperm head. In the late pronuclear stage following ICSI with an isolated sperm head, microtubule organization was the same as in late pronuclear stage eggs after intact sperm injection. The first mitotic spindle was organized in eggs following ICSI with an isolated sperm head, as observed in eggs following ICSI with an intact sperm. Conclusions: These results indicate that the MTOC is in oocyte cytoplasm during fertilization and fulfils the function when the sperm centrosome is absent. (Reprod Med Biol 2005; 4: 169–178)